The Capability of Total Protein Extracted from Black Sea Cucumbers (Holothuria leucospilota) in Agglutinating of Mouse Sperms (Mus musculus) - Haryanto, Hery; Ruyani, Aceng; Piramida, Cally (Proceeding International Conference on Global Resource Conservation, 2015)
The research aimed to know the effect of total protein extracted from black sea cucumbers (Holothuria leucospilota) on agglutination of mouse sperms (Mus musculus). The flesh of black sea cucumber  was homogenized in Tris Buffer Saline (TBS) at pH 7.4. The homogenate was added with ammonium sulphate 50%(w/v) for presipitating protein. The presipated protein was purified with 12.000 MWCO dialysis bag to remove ammonium sulphate. The purified protein was quantitated with Biuret Method. The concentration of purified protein was 4,97g/dL. There were five concentration proteins used mouse sperm agglutination test, i.e. 4.97, 3.52, 2.48, 1.17 g/dL and 0% (control). Mouse sperm suspension was prepared by soaking an epypydimal duct in 0,9% (w/v) NaCl solution. The purified protein in varied concentration was then used for agglutination of suspension of mouse sperm. This research used Completely Randomized Design (CRD) with 5 concentrations of protein  and 5 replications. The data of this research were analyzed by using ANOVA. The result showed that total protein extract of black sea cucumberwas significantly different on mouse sperm agglutination. The fastest time of agglutination of was indicated by concentrations of  4.97 g/dL. total proten of black sea cucumber. Keywords: Black Sea Cucumber (Holothuria leucospilota); mouse sperm suspension; sperm agglutination; total protein extract